Changing arenas for agricultural climate change adaptation in Vietnam. Issue 2 (17th February 2017) - Christoplos, Ian; Ngoan, Le Duc; Sen, Le Thi Hoa; Huong, Nguyen Thi Thanh; Nguyen, Huy
ABSTRACT: Great changes are underway in how climate and agricultural risks are managed in Vietnam. Uncertainties are emerging regarding the role of the state in managing these risks and what this implies for assumptions regarding hoped-for climate change transformations. Local government control is waning in relation to the expanding roles of the private sector and the growing autonomy of farmers themselves. This article presents cases that illustrate the ways that farmers, private investors, and local authorities are responding to climate risk within roles relating to the other risks involving markets, food security, and pressures on common property resources.